Determination of seismic wave of consolidated granite rock in Penang Island: Ultrasonic testing method vs seismic refraction method - Mohd Hafiz Musa, Zulfadhli Hasan Adli, MN Khairul Arifin, . (2010)
In seismic survey, the information regarding the velocity of compression wave (Vp) as well as shear wave (Vs) are very useful especially during the seismic interpretation. Previous studies showed that both Vp and Vs determined by above methods are totally different with respect to each other but offered good approximation. In this study, both Vp and Vs of consolidated granite rock were studied by using ultrasonic testing method and seismic refraction method. In ultrasonic te sting, two different condition of rock are used which is dry and wet. The differences between Vp and Vs getting by using ultrasonic testing and seismic refraction were investigated and studied.